THE INFLUENCE OF ROLE MODELS, ENTREPRENEURSHIP EDUCATION, AND SELF-EFFICACY ON ENTREPRENEURSHIP INTENTIONS IN CLASS XI STUDENTS OF SMKN 46 JAKARTA - Andena Noviyati Nabila; Corry Yohana; Aditya Pratama (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2023)
The purpose of this study was to determine how the influence of role models, entrepreneurship education, and self-efficacy on entrepreneurial intentions in class XI students of SMKN 46 Jakarta. The study was conducted for approximately six months starting from February 2022 to July 2022. The population was taken from class XI students of SMKN 46 Jakarta with a sample of 168 students. This type of research is quantitative research using a survey method in the form of a questionnaire distributed online via Microsoft Form. The data analysis model used is Structural Modeling-Partial Least Square (SEMPLS) and uses SmartPLS 3.0 software to analyze the data. The output of this study shows that role models, entrepreneurship education, and self-efficacy have a positive and significant effect on entrepreneurial intentions.